ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN KOPERASI SIMPAN PINJAM PEGAWAI PADA PENGADILAN AGAMA JAMBI KELAS 1A - Handini, Nurul Sri; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2019)
The Jambi Class 1A Religion Court Employee Cooperative as a business entity that has many activitiesand work programs also needs a system to be able to process data to get the information they need ontheir savings and credit units. Judging from the current system in Jambi 1 Class Religious CourtEmployees Cooperative, especially in the field of savings and loans, it is still not effective because thereare still problems such as difficulty in managing data, both in the form of member data, loan data andinstallment data that are still in book form. In the process the data is sometimes lost and damaged, there isoften an error in recording the sum of both loans and deposits, there are delays in making reports. Thesolution offered is to use a web-based information system through which this system makes it easy forvisitors and cooperative members to obtain information quickly. The system modeling tool used is UML(Unified Modeling Language). The output produced is in the form of a prototype with a report on theresults of the business, return data reports, borrowing data reports, and member data reports